The silent and dangerous inequity around access to COVID-19 testing: a call to action - Batista, Carolina; Hotez, Peter; Amor, Yanis Ben; Kim, Jerome H; Kaslow, David; Lall, Bhavna; Ergonul, Onder; Figueroa, J Peter; Gursel, Mayda; Hassanain, Mazen; Kang, Gagandeep; Larson, Heidi; et al. (EClinicalMedicine, 2022)
COVID-19 vaccines have proven safe and efficacious in reducing severe illness and death. Cuban protein subunit vaccine Abdala has shown safety, tolerability and efficacy (92·3% [95% CI: 85·7‒95·8]) against SARS-CoV-2 in clinical trials. This study aimed to estimate Abdala's real-world vaccine effectiveness (VE). - This retrospective cohort study in Havana analyzed Cuban Ministry of Public Health databases (May 12-August 31, 2021) to assess VE in preventing severe illness and death from COVID-19 (primary outcomes). Cox models accounting for time-varying vaccination status and adjusting by demographics were used to estimate hazard ratios. A subgroup analysis by age group and a sensitivity analysis including a subgroup of tested persons (qRT-PCR) were conducted. Daily cases and deaths were modelled accounting for different VE. - The study included 1 355 638 persons (Mean age: 49·5 years [SD: 18·2]; 704 932 female [52·0%]; ethnicity data unavailable): 1 324 vaccinated (partially/fully) and 31 433 unvaccinated. Estimated VE against severe illness was 93·3% (95% CI: 92·1-94·3) in partially- vaccinated and 98·2% (95% CI: 97·9-98·5) in fully-vaccinated and against death was 94·1% (95% CI: 92·5-95·4) in partially-vaccinated and 98·7% (95% CI: 98·3-99·0) in fully-vaccinated. VE exceeded 92·0% in all age groups. Daily cases and deaths during the study period corresponded to a VE above 90%, as predicted by models. - The Cuban Abdala protein subunit vaccine was highly effective in preventing severe illness and death from COVID-19 under real-life conditions. - Cuban Ministry of Public Health. Genetic Engineering and Biotechnology Centre.